Monetary Policy Pass Through Considering the Reserve Ratio and Policy Rate in Nepal: An Empirical Gaze Using SVAR Analysis - Pokhrel, Aditya; Upreti, Shubham (Economic Review of Nepal, 2025)
Utilizing the monthly data from July 2017 to July 2024, this study attempts to analyze the monetary pass through in Nepal with the use of the reserve requirements (quantity) and the repo rate (price) on the base rate and the lending rates. The study fits a 2 lagged VAR and recursively identified SVAR. An interaction term of repo rate and CRR has been used which represents the effects of liquidity constraints. All the series are I (1) using the PP test. Results reveal that a one percentage point increase in repo rate increases the base rate by 0.32 percentage points and the lending rate by 0.45 percentage points (after two months). The corresponding increase in the CRR, increases both the rates by around 0.22 percentage points. A positive and statistically weak interaction term signifies that there's a lame synergy effect. The SVAR impulse responses notify the repo shocks account for 50 percent of the forecast error variance in lending rates over a 12-month period contrasting to the CRR shocks (as 10–15 percent). The pass-through is quicker than with pre-corridor research, however the structural liquidity frictions hinders it to be complete. There is a possibility that Nepal's interest rate-based channel and policy efficiency might be improved by reducing the range of the corridor, adding a counter-cyclical modification to the CRR, and changing the modality of the base rate.